The Effect of The T.A.S.C Model on Mathematics Achievement And Their Mathematical Communication Skills For Fifth Primary Grade Students (Journal of the College of Basic Education, 2024)
The aim of the research is to identify the effect of the T.A.S.C model on the mathematical communication skills of fifth-grade primary school students. The research sample consisted of (59) male and female students (after excluding the failing students) from fifth-grade primary school students in (Al-Takatuf Mixed Primary School) affiliated with the General Directorate of Education in Diyala / District. Baquba/Bani Saad district, for the first semester of the academic year (2023-2024), and by random selection, Division (B) was chosen to represent the experimental group that was studied according to the T.A.S.C model, and its number reached (30) male and female students, and Division (A) was chosen to represent the control group. The number of students was (29) students, which were studied according to the usual method, and the two groups were rewarded in the following variables (intelligence, chronological age in months, previous achievement in mathematics, and previous mathematical knowledge.The research tool was prepared: the sports communication skills test. The test consisted of (25) essay items, and included (5) items for each of the sports communication skills, which are (the sports reading skill, the sports writing skill, the sports acting skill, the sports discussion skill, and the sports speaking skill). The validity and reliability of the Mathematical Communication Test was confirmed, using the (Cronbach’s Alpha) equation, as the reliability value of the Mathematical Communication Test items reached (0.80).After completing the experiment, a sports communication skills test was applied to the two groups (experimental and control). After collecting data and using statistical methods, the results of the research were as follows:There is a statistically significant difference at the significance level (0.05) between the average scores of the two groups (experimental and control) on the sports communication skills test, in favor of the experimental group. In light of the research results, a number of conclusions, recommendations and proposals were reached.